Effects of straw returning combined with earthworm addition on nitrification and ammonia oxidizers in paddy soil - Chu, Xiangqian; Bai, Naling; Zheng, Xianqing; Wang, Quanhua; Pan, Xi; Li, Shuangxi; Zhang, Juanqin; Zhang, Haiyun; He, Wenjie; Zhong, Feng; Lv, Weiguang; Zhang, Hanlin (Frontiers in Microbiology, 2022)
Soil ammonia oxidation, which acts as the first and rate-limiting step of nitrification, is driven by ammonia-oxidizing bacteria (AOB), ammonia-oxidizing archaea (AOA) and complete ammonia oxidizer (comammox, amoA gene of clade-A and clade-B). Straw returning, widely used ecological technology in China, is an effective measure for promoting straw decomposition and soil nutrient cycling when combined with earthworm addition. However, the effects of straw returning combined with earthworm addition on soil ammonia oxidizers remain poorly understood. A 2-year plot experiment was conducted with 5 treatments: no fertilizer (CK); regular fertilization (RT); straw returning (SR); earthworm addition (W); straw returning + earthworm addition (SRW). The AOA, AOB, comammox clade-A and clade-B community microbial diversities and structures were investigated by high-throughput sequencing. The results showed that (1) compared to RT treatment, W, SR, and SRW treatments all significantly increased the richness of AOA and comammox clade-A and clade-B (P<0.05), and the richness of AOB was only significantly promoted by SRW treatment (P<0.05). However, only SRW had a higher comammox clade-B diversity index than RT. (2) The ammonia oxidizer community structures were altered by both straw returning and earthworm addition. Soil NH4+-N was the critical environmental driver for altering the ammonia oxidizer community structure. (3) Compared with RT treatment, the soil potential nitrification rate (PNR) of W and SRW treatments increased by 1.19 and 1.20 times, respectively. The PNR was significantly positively correlated with AOB abundance (path coefficient = 0.712, P < 0.05) and negatively correlated with clade-B abundance (path coefficient = −0.106, P<0.05). This study provides scientific support for the application of straw returning combined with earthworm addition to improve soil nitrification with respect to soil ammonia-oxidizing microorganisms.